The Influence of Organizational Commitment, Job Satisfaction and Perceptions of Supervisor Support on Turnover Intention (Study at PT. Jepe Press Media Utama) - Agung Putra Kurniawan; Novelia Asita Mranani; Supartini (Journal of Economy, Accounting and Management Science (JEAMS), 2023)
Business competition in the current era of globalization is getting tougher. Intense competition makes companies try to maintain their human resources. Human resources are company assets that are very valuable, therefore the existence of human resources is very necessary in achieving company goals. The purpose of this study is to determine the effect of organizational commitment, job satisfaction and perceptions of supervisor support simultaneously and partially on turnover intention at PT. Jepe Press Media Utama. The sample of this research is the employees of PT. Jepe Press Media Utama, with a total sample of 80 respondents. The analysis technique uses Multiple Linear Regression with the SPSS program or software. The results showed that simultaneously (simultaneous) showed that organizational commitment, job satisfaction and perceptions of supervisor support had an effect on turnover intention, partially organizational commitment had a positive and significant effect on turnover intention, job satisfaction had a positive and significant effect on turnover intention, and perceptions of supervisor support do not have a positive and significant effect on turnover intention.